STUDI TINGKAT PENGETAHUAN DAN PERSEPSI TENAGA KESEHATAN MENGENAI PERANAN FARMAKOGENOMIK - Muhammad Akib Yuswar; Robiyanto Robiyanto; Eka Kartika Untari; Shoma Rizkifani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
Research on the extent to which health practitioners in West Kalimantan understand the important role of pharmacogenomics have not been reported to date. West Kalimantan (Kalbar) is known as a province characterized by three main ethnicities, namely Chinese, Malay and Dayak. Therefore, the potential application of pharmacogenomics for the treatment of patients in health facilities across the province is very possible. This study aimed to measure the level of knowledge and perceptions of health practitioners (participants) about the role of pharmacogenomics in patient treatment plans. This research is descriptive with a questionnaire-based survey method. The data analyzed is primary data from the answers of participants to the online questionnaire. Based on the responses of 106 participants (involving doctors, pharmacists, nurses, midwives, and others) from various cities and districts in West Kalimantan, it was found that the level of knowledge was very good (75.5%), good (17.0%), and not good. (7.5%). The level of participants' perceptions of the role of pharmacogenomics are those who have positive perceptions (97.2%) and negative perceptions (2.8%). It can be concluded that 75% of health practitioners in West Kalimantan have a very good level of knowledge and 97% of them own a positive perception of the importance of pharmacogenomics.